Impact of anemia on the association between red cell distribution width and 1-year mortality in acute heart failure patients - Maita-Arauco, Sherelym Alessandra (2025)
Background: Different accessible and low-cost biomarkers have been investigated to stratify patients with acute heart failure (AHF). One of them is the red cell distribution width (RDW), which proved to be a greater prognostic marker of mortality than other conventional markers. Objective: Therefore, the objective of our study is to determine whether the anemic status modifies the magnitude of association between high RDW and 1-year mortality in patients with AHF. Design: Observational, analytical, retrospective cohort study. Methods: We included participants ⩾18 years old hospitalized with a diagnosis of AHF. As an association measure, a crude and adjusted generalized linear model of the Poisson family calculated the risk ratio (RR) with a 95% confidence interval (95% CI). Results: In all, 709 participants with an average age of 73.48 years were included. At 1 year, the risk of dying was three times higher with high RDW (RR = 3.05, 95% CI: 1.39–6.66; p < 0.01). In anemic participants, the risk of dying at 1 year is two times greater with high RDW (RR = 2.18, 95% CI: 0.91–5.22; p = 0.07), while in non-anemic participants, the risk of dying increased almost seven times (RR = 6.95, 95% CI: 1.65–29.23; p < 0.01). Conclusion: High RDW is a risk factor for mortality at 1 year in patients with AHF. A greater magnitude of association was found in non-anemic patients. © The Author(s), 2025.